DESIGNING TRUSTED HEALTH INFORMATION SPACES: THE CASE OF THE WINDOWS OF KNOWLEDGE - Ragacini, Leonardo Adriano (Seven Editora, 2025)
In a context marked by an infodemic and the widespread circulation of low-quality content, digital curation becomes a central strategy for ensuring access to reliable health information. This chapter analyses the Windows of Knowledge (WoK) of BIREME/PAHO/WHO as a concrete example of a curation infrastructure implemented within the framework of the Virtual Health Library. Drawing on a literature review on digital curation, information lifecycle and preservation models, in combination with institutional technical documents, it examines the informational architecture of the Windows, their flows of content selection, validation and updating, as well as the technical and organisational requirements for their maintenance. Issues such as usability, accessibility, interoperability with other health platforms and the challenges of continuous updating in highly dynamic knowledge domains are discussed. A SWOT-type analysis explores the initiative’s strengths and weaknesses, highlighting opportunities for expansion to new themes and audiences. Concrete examples, such as the Windows dedicated to COVID-19, Mpox, health promotion and the commercial dimension of the determinants of health, illustrate how digital curation can support public policies, health education and evidence-informed decision-making. Finally, the chapter proposes recommendations to strengthen similar initiatives in other institutional contexts.DOI: https://doi.org/10.56238/sevened2025.036-083